Long-term mortality after blood pressure-lowering and lipid-lowering treatment in patients with hypertension in the Anglo-Scandinavian Cardiac Outcomes Trial (ASCOT) Legacy study: 16-year follow-up results of a randomised factorial trial. Issue 10153 (29th September 2018) - Gupta, Ajay; Mackay, Judith; Whitehouse, Andrew; Godec, Thomas; Collier, Tim; Pocock, Stuart; Poulter, Neil; Sever, Peter
Summary: Background: In patients with hypertension, the long-term cardiovascular and all-cause mortality effects of different blood pressure-lowering regimens and lipid-lowering treatment are not well documented, particularly in clinical trial settings. The Anglo-Scandinavian Cardiac Outcomes Trial (ASCOT) Legacy Study reports mortality outcomes after 16 years of follow-up of the UK participants in the original ASCOT trial. Methods: ASCOT was a multicentre randomised trial with a 2 × 2 factorial design. UK-based patients with hypertension were followed up for all-cause and cardiovascular mortality for a median of 15·7 years (IQR 9·7–16·4 years). At baseline, all patients enrolled into the blood pressure-lowering arm (BPLA) of ASCOT were randomly assigned to receive either amlodipine-based or atenolol-based blood pressure-lowering treatment. Of these patients, those who had total cholesterol of 6·5 mmol/L or lower and no previous lipid-lowering treatment underwent further randomisation to receive either atorvastatin or placebo as part of the lipid-lowering arm (LLA) of ASCOT. The remaining patients formed the non-LLA group. A team of two physicians independently adjudicated all causes of death. Findings: Of 8580 UK-based patients in ASCOT, 3282 (38·3%) died, including 1640 (38·4%) of 4275 assigned to atenolol-based treatment and 1642 (38·1%) of 4305 assigned to amlodipine-based treatment. 1768 of the 4605 patients in the LLA died, including 903 (39·5%) of 2288 assigned placebo and 865 (37·3%) of 2317 assigned atorvastatin. Of all deaths, 1210 (36·9%) were from cardiovascular-related causes. Among patients in the BPLA, there was no overall difference in cardiovascular mortality between treatments (adjusted hazard ratio [HR] 0·90, 95% CI 0·81–1·01, p=0·0776]), although significantly fewer deaths from stroke (adjusted HR 0·71, 0·53–0·97, p=0·0305) occurred in the amlodipine-based treatment group than in the atenolol-based treatment group. There was no interaction between treatment allocation in the BPLA and in the LLA. However, in the 3975 patients in the non-LLA group, there were fewer cardiovascular deaths (adjusted HR 0·79, 0·67–0·93, p=0·0046) among those assigned to amlodipine-based treatment compared with atenolol-based treatment (p=0·022 for the test for interaction between the two blood pressure treatments and allocation to LLA or not). In the LLA, significantly fewer cardiovascular deaths (HR 0·85, 0·72–0·99, p=0·0395) occurred among patients assigned to statin than among those assigned placebo. Interpretation: Our findings show the long-term beneficial effects on mortality of antihypertensive treatment with a calcium channel blocker-based treatment regimen and lipid-lowering with a statin: patients on amlodipine-based treatment had fewer stroke deaths and patients on atorvastatin had fewer cardiovascular deaths more than 10 years after trial closure. Overall, the ASCOT Legacy study supports the notion that interventions for blood pressure and cholesterol are associated with long-term benefits on cardiovascular outcomes. Funding: Pfizer.